Self-Leadership and Empowering Leadership in a Western Balkan Context - Nientied, Peter; Toska, Merita (International Review of Management and Marketing, 2021)
In to-day’s dynamic business world, a trend is towards more flexible organisations with enhanced autonomy and self-leadership of employees and teams. This study introduces the concepts of self-leadership and empowering leadership in the Western Balkans. The study measures employed professionals’ views of self-leadership and experienced empowering leadership. Special attention is given to possible differences in views by gender and by professionals with / without a leadership role. Two instruments are applied, the Revised Self-Leadership Questionnaire and the Empowering Leadership Survey (n=265). Subsequently interviews were conducted with 10 company directors to generate their viewpoints and experiences of self-leadership and empowering leadership. Results show correlations between self-leadership and empowering leadership and show differences between men’s and women’s reports. The study also notes that better understanding the potential of empowering leadership leading to more self-leadership demands another type of research. A discussion of the study and suggestions for future research conclude the article. Keywords: self-leadership, empowering leadership, self-management, Western Balkans, Albania JEL Classifications: M12, M19, M54 DOI: https://doi.org/10.32479/irmm.10893